Facilitation of dopamine‐dependent long‐term potentiation in the medial prefrontal cortex of male rats follows the behavioral effects of stress. Issue 2 (20th September 2020) - Lamanna, Jacopo; Isotti, Francesco; Ferro, Mattia; Racchetti, Gabriella; Anchora, Lavinia; Rucco, Daniele; Malgaroli, Antonio
Abstract: The effect of stress on animal behavior and brain activity has been attracting growing attention in the last decades. Stress dramatically affects several aspects of animal behavior, including motivation and cognitive functioning, and has been used to model human pathologies such as post‐traumatic stress disorder. A key question is whether stress alters the plastic potential of synaptic circuits. In this work, we evaluated if stress affects dopamine (DA)‐dependent synaptic plasticity in the medial prefrontal cortex (mPFC). On male adolescent rats, we characterized anxiety‐ and depressive‐like behaviors using behavioral testing before and after exposure to a mild stress (elevated platform, EP). After the behavioral protocols, we investigated DA‐dependent long‐term potentiation (DA‐LTP) and depression (DA‐LTD) on acute slices of mPFC and evaluated the activation of DA‐producing brain regions by western and dot blot analysis. We show that exposure to the EP stress enhances DA‐LTP and that desipramine (DMI) treatment abolishes this effect. We also found that DA‐LTD is not affected by EP stress unless when this is followed by DMI treatment. In addition, EP stress reduces anxiety, an effect abolished by both DMI and ketamine, while motivation is promoted by previous exposure to EP stress independently of pharmacological treatments. Finally, this form of stress reduces the expression of the early gene cFOS in the ventral tegmental area. These findings support the idea that mild stressors can promote synaptic plasticity in PFC through a dopaminergic mechanism, an effect that might increase the sensitivity of mPFC to subsequent stressful experiences. Abstract : Stress enhances dopamine (DA)‐long‐term potentiation but desipramine (DMI) abolishes this effect. DA‐long‐term depression is not affected unless when stress is followed by DMI. Stress reduces anxiety, an effect abolished by DMI/ketamine while motivation is always promoted. Stress also reduces cFOS expression in the ventral tegmental area in all conditions.